IMPLEMENTASI PROGRAM GEBYAR ANAK SHOLEH SEBAGAI UPAYA PENGUATAN KARAKTER RELIGIUS ANAK USIA DINI DAN SEKOLAH DASAR DI DESA TELUK MELINTANG - Maryam; Pahmi; Sofiatun Nisa; M. Kausar; Imroatul Pitri; Mayang Sari; Madani Futra; Eti Lastriani; Rita Yani; Solmah; Nur hapizin; Diki Nurdwiyanto (As-Sulthan Journal of Education, 2026)
The Community Service Program (KKN) is a form of student community service aimed at making a real contribution to social and educational development. One of the programs implemented was the "Gebyar Anak Sholeh" (Sholeh Children's Celebration) event, aimed at strengthening the religious character of early childhood and elementary school children in Teluk Melintang Village. This activity took place on January 18th from 9:00 AM to 12:00 PM WIB at the Nurul Falah Mosque. Competitions included the call to prayer (azan) (14 elementary school participants), daily prayer memorization (15 elementary school participants), and mosque coloring (30 early childhood education participants). The daily prayer memorization topics included prayers for eating, prayers after eating, prayers for entering the mosque, prayers for leaving the mosque, prayers before going to bed, prayers for waking up, and prayers for both parents. The implementation method used a participatory approach through educational competitions combined with coaching and motivation. The results demonstrated high enthusiasm from the participants and increased self-confidence and understanding of children's daily worship practices. This program is effective in fostering children's religious character and can be replicated as a model for mosque-based educational activities at the village level.